THE INFLUENCE OF GOOD CORPORATE GOVERNANCE AND FIRM SIZE ON CAPITAL STRUCTURE AND FIRM FINANCIAL PERFORMANCE (AN EMPIRICAL RESEARCH AT BANKS LISTED ON INDONESIA STOCK EXCHANGE IN THE PERIODS OF 2011-2013) - Puspaliliah, Hajar Cherry; Nimran, Umar; Kertahadi, Kertahadi (Profit: Jurnal Adminsitrasi Bisnis, 2014)
The purpose of this research is to investigate the relationship between good corporate governance and firm size on capital structure and firm financial performance of banks listed on Indonesia Stock Exchange during a three year period. A type of research used in this research is explanatory research with quantitative approach. Technique that will be used in the data collection in this research is using the method of documentation. Populations and samples in this study is secondary data on the bank companyâ€™s on Indonesia Stock Exchange (IDX) Corner Faculty of Economics, University of Brawijaya Malang with the number of sample is 19 and sampling method used in this research is purposive sampling technique. Data analysis method in this research using Partial Least Square (PLS). The result show a nonsignificant negative influence of good corporate governance on capital structure. Firm size significantly negative influence on capital structure. Good corporate governance has a positive significant influence on financial performance. Firm size nonsignificant positive on financial performance. Capital structure has a negative significant influence on financial performance. Â  Keywords : Good Corporate Governance, Firm Size, Capital Structure, Firm Financial Performance